2021
DOI: 10.1155/2021/5518946
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use and Its Associated Factors among Adolescents Aged 15–19 Years at Governmental High Schools of Aksum Town, Tigray, Ethiopia, 2019: A Cross-Sectional Study

Abstract: Introduction. The impact of alcohol use among adolescents is multidisciplinary and affects the adolescent’s academic performance, precipitates with sexually transmitted infections or psychiatric disorders, and disturbs the social domain of adolescents. Therefore, this study aimed to assess the prevalence and associated factors of alcohol use among adolescents aged 15–19 years at the governmental high schools of Aksum Town, Tigray, Ethiopia, in 2019. Methods. A facility-based cross-sectional study was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Among the respondents with age bracket of 15-19 years, alcoholic beverage consumption rate was 40.5%, poly substance use (24.3%), cigarette (21.7%), cannabis (6.8) and 4.1% of codeine. This result is in agreement with the survey conducted in Abakaliki by [10], which revealed that the rate alcohol, and cigarette use were more common among students between the age of 15-19 years olds (90.8%, and 44.6% respectively); also line with research conducted by [17] that implicated alcohol use (39.7%) among 15-19 years adolescents as the highest substance being consumed by this category of age band; also similar to [1] report, which demonstrated that monthly heavy episodic drinking among young people between 15 and 19 years (11.7%) was high when compared with older population (7.5%).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Among the respondents with age bracket of 15-19 years, alcoholic beverage consumption rate was 40.5%, poly substance use (24.3%), cigarette (21.7%), cannabis (6.8) and 4.1% of codeine. This result is in agreement with the survey conducted in Abakaliki by [10], which revealed that the rate alcohol, and cigarette use were more common among students between the age of 15-19 years olds (90.8%, and 44.6% respectively); also line with research conducted by [17] that implicated alcohol use (39.7%) among 15-19 years adolescents as the highest substance being consumed by this category of age band; also similar to [1] report, which demonstrated that monthly heavy episodic drinking among young people between 15 and 19 years (11.7%) was high when compared with older population (7.5%).…”
Section: Discussionsupporting
confidence: 92%
“…Finding from the study conducted in Zaria Nigeria, reported that the current prevalence of psychoactive substances by young people was 46% [16]. Study conducted by [17] reported that the proportion of alcohol use (39.7%) among 15-19 years was found to be higher than other age brackets. In the research conducted in Republic of Palau had revealed that the proportion of current alcohol drinking was higher in young adult aged 21-24years than in those aged; most smokers in low-and middleincome countries start smoking in the early twenties [18].…”
Section: Introductionmentioning
confidence: 99%
“…In this research, alcohol usage in Nekemte town is prevalent, with a rate of 27.84%. Other research reveals the respective prevalence in other places: Aksum Town, Ethiopia, 39.7%; 11 Addis Ababa, Ethiopia, 45.7%; 12 South Africa, 39.1%; 13 the United States of America, 41.8%; 14 Kisumu, Kenya, 51.9%; 15 Brazil, 46.9%; 16 and Tanzania, 32.5%. 17 Upon comparing the aforementioned prevalence rates, Nekemte town’s rate is much lower than that of other places in Ethiopia as well as other countries.…”
Section: Discussionmentioning
confidence: 95%
“…Current alcohol use: students who answered “Yes” to the question “have you ever drunk at least one of the alcoholic beverages (beer, wine, whiskey, Areki, Tela, Tej, etc.) for nonmedical purposes in the last three months?” were considered current alcohol users [ 73 , 74 ].…”
Section: Methodsmentioning
confidence: 99%